Stenochlaena palustris Ethanol Extract Decreases Viability and Induces G1-Phase Cell Cycle Arrest in HSC-3 Tongue Cancer Cells via p21 and p27 - Sandra, Ferry; Ranggaini, Dewi; Halim, Johni; Taramalinda, Elizabeth Yuliani; Scania, Alifah Evi; Roeslan, Boedi Oetomo; Lee, Kyung Hoon (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Oral squamous cell carcinoma (OSCC) of the tongue is an aggressive cancer with a poor prognosis due to its resistance to standard treatments. Stenochlaena palustris, a medicinal fern containing bioactive compounds, has shown potential anticancer properties. However, there is a lack of studies addressing the effects of S. palustris ethanol extract (SPEE) on tongue cancer. This study examined the effects of SPEE on the cell viability and cell cycle of human squamous cell carcinoma (HSC)-3 tongue cancer cells.METHODS: SPEE was prepared with the maceration method. HSC-3 cells were treated with SPEE at concentrations of 100, 500, and 1000 µg/mL for 24 and 48 hours. Cell viability was measured with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Cell cycle analysis was performed using flow cytometer. Immunoblotting was used to measure amount of cell cycle regulators, protein 21 (p21) and protein 27 (p27).RESULTS: SPEE treatment led to a significant decrease in HSC-3 viable cells in a concentration- and time-dependent manner, with the most pronounced effect at higher concentration and prolonged treatment time. There was a slightly increase in the percentage of cells in the Sub-G1 phase in SPEE-treated group, meanwhile there was a significant increase in the percentage of cells in the G1-phase. Increased amount of p21 and p27 were observed in SPEE-treated group.CONCLUSION: SPEE significantly inhibited HSC-3 cell proliferation in a concentration- and time-dependent manner, primarily by inducing G1-phase cell cycle arrest through the upregulation of p21 and p27. Taken together, SPEE could be a potential anti-cancer agent for tongue cancer cell. KEYWORDS: Stenochlaena palustris, tongue cancer, cytotoxic, cell cycle arrest, HSC-3 cells, p21, p27